Application of high-throughput sequencing in citrus virus identification and analysis of population diversity - LI Xiang; YANG Jin; HUANG Aijun; ZHOU Jun; YI Long (Guoshu xuebao)
Citrus, as an important component of global economic crops, is the world's largest category of fruit. However, citrus is also a host for many viruses and bacterial pathogens, and its production conditions are threatened by various viral diseases. These diseases are widely distributed worldwide, causing severe impacts on the yield and quality of citrus, resulting in significant economic losses. The viruses that severely affect the citrus industry mainly include: citrus tristeza virus (CTV), citrus chlorotic dwarf-associated virus (CCDaV), citrus tatter leaf virus (CTLV), citrus yellow vein clearing virus (CYVCV), citrus psorosis virus (CPsV), citrus vein enation virus (CVEV), citrus exocortis viroid (CEVd), citrus leaf blotch virus (CLBV), citrus sudden death-associated virus (CSDaV), and satsuma dwarf virus (SDV), etc. Among them, CTV is one of the most destructive viral diseases in the citrus industry, leading to reduced citrus yield and quality, weakened tree vigor, and even death. CTV, a positive single-stranded RNA virus in the Closteroviridae family, exhibits significant genetic diversity and strain differentiation, resulting in varying pathogenicity. Based on symptoms and genomic sequences, it can be classified into quick decline, stem pitting, and yellow shoot strains. CYVCV, belonging to the Mandarivirus genus of the Alphaflexiviridae family, has a positive single-stranded RNA genome. Transmitted among citrus plants by citrus mealybugs, contaminated tools, it causes leaf wrinkling, chlorosis mottling, and yellow vein clearing in lemons, posing a global threat. CTLV, a Capillovirus genus virus in the Betaflexiviridae family, is an ASGV strain, seriously harming citrus production. CLBV, a Betaclosteroviridae family Citrivirus genus member, is a positive single-stranded RNA virus with filamentous, wavy particles, infecting diverse hosts mainly via grafting and seeds. Lately, citrus viral diseases are on the rise, yet some pathogens remain undetermined, such as citrus cristacortis disease. Citrus-infecting viruses often have latency and are hard to detect directly. Therefore, accurate detection and identification of citrus viruses play a central role in the disease control system. In recent years, with the rapid advancement of molecular biology technology, rapid and accurate virus identification and in-depth study of their genetic diversity have become key to ensuring the healthy development of the citrus industry. citrus virus detection and identification are mainly based on the biological characteristics, physical characteristics of virus particles, protein characteristics, and nucleic acid characteristics to establish some methods. At present, the conventional detection and identification methods for citrus viruses mainly include biological indexing, electron microscopy, serological detection, and molecular biological detection. The above methods are well-suited for known viruses and can be combined with multiple methods for detection and identification. However, when it is necessary to accurately identify unknown viruses or newly emerging viruses, the above methods are difficult to work. With the emergence of high-throughput sequencing (HTS) technology in recent years, the above problems have been solved. This technology uses the principle of sequencing by synthesis, which can sequence a large number of RNA and DNA molecules in a short time without prior knowledge of the virus's biological characteristics or genome structure, thus obtaining its nearly complete genomic sequence. This capability solves the limitations of traditional methods when facing unknown viruses and greatly accelerates the discovery and identification process of new viruses. Through HTS technology, researchers have revealed many previously unknown virus types and deepened the understanding of the genetic diversity of known viruses, providing a scientific basis for targeted control strategies. HTS technology also shows great potential in population diversity analysis. By sequencing a large number of virus samples, researchers can obtain rich genetic sequence data, thereby analyzing the genetic variation of viruses, evolutionary trajectories, and their interactions in the ecosystem. This provides a powerful tool for understanding the mechanisms of viral diseases, predicting virus variation trends, and assessing the effectiveness of control measures. Although HTS has achieved significant results in citrus virus research, it still faces some challenges. For example, the complexity of data analysis and the need for bioinformatics knowledge limits its popularization and application in some areas; the high cost of sequencing is still a major obstacle for resource-limited areas. In the future, with the continuous development and optimization of technology, HTS will play a more important role in the identification of citrus viruses and population diversity analysis, providing strong support for the sustainable development of the citrus industry. This article reviews the latest progress of HTS in the detection and identification of citrus viruses, as well as the challenges and future prospects in citrus virus research.